Self-adaptive encryption algorithm for image based on affine and composed chaos - Chang-ci WEN; Qin WANG; Fu-min HUANG; Zhi-shu YUAN; Chun-sheng TAO (Tongxin xuebao)
On the basis of three-dimensional affine transformation in limited integer domain and composed chaos,a novel digital image encryption algorithm was proposed.Firstly,it scrambled pixels’ position and confused pixels’ value according to corresponding coordination.Secondly,it took a series of nonlinear diffusion,substitution and re-diffusion.In the process of substitution,it introduced pixels’ value to perturb multiple chaos systems that were coupled together for self-adaptive encryption.The algorithm proceeded the above two steps for 3 times to defend chosen plaintext attack,and had huge key space to defend violent attack.The scrambling function in it was compatible with images at any ratio of length to width without any preprocessing; the constructed whole chaos system which had a simple form was designed modularly,and could be realized parallel conveniently.